Lending implications of U.S. bank stress tests: Costs or benefits? - Acharya, Viral V.; Berger, Allen N.; Roman, Raluca A. (Journal of Financial Intermediation, 2018)
The U.S. bank stress tests aim to improve financial system stability. However, they may also affect bank credit supply. We formulate and test opposing hypotheses about these effects. Our findings are consistent with the Risk Management Hypothesis, under which stress-tested banks reduce credit supply−particularly to relatively risky borrowers−to decrease their credit risk. The findings do not support the Moral Hazard Hypothesis, in which these banks expand credit supply−particularly to relatively risky borrowers that pay high spreads−increasing their risk. Results are generally stronger for safer banks, banks that passed the stress tests, and the earlier stress tests.